Echocardiographic Findings in Patients with Atrial Septal Aneurysm: A Prospective Case-Control Study - Ramazan Atak; Mehmet Ileri; Selcuk Ozturk; Ahmet Korkmaz; Ertan Yetkin (Cardiology Research and Practice)
Background. Atrial septal aneurysm (ASA) is a congenital deformity of the interatrial septum with a prevalence of 1-2% in the adult population. Although ASA has been supposed to be an incidental finding in echocardiographic examination, its structural and clinical associations have gained an increasing interest. Aim. To investigate and compare the clinical features and echocardiographic parameters between ASA patients and age- and gender-matched control group patients. Methods. 410 patients with ASA were enrolled in the study, prospectively. After the exclusion of 33 patients, the remaining 377 patients comprised the study group. The control group consisted of 377 age- and gender-matched patients without ASA. Results. Aortic valve regurgitation and mitral valve regurgitation were more often observed in patients with ASA, and percentages of patients with ascending aortic aneurysm (AAA), patent foramen ovale (PFO), and atrial septal defect (ASD) were higher in ASA patients compared to control group patients. Aortic root diameter was larger in ASA patients compared to control group patients (29.2 ± 3.9, 28.6 ± 3.1, p=0.05, respectively). Ascending aorta diameter was higher in ASA patients compared to patients without ASA (44 ± 0.3, 41.5 ± 0.2, p=0.02). Logistic regression analysis revealed that mitral valve regurgitation (OR: 2.05, 95% CI : 1.44–2.92, p<0.001) and PFO (OR: 11.62, 95% CI : 2.64–51.02, p=0.001) were positively and independently associated with the presence of ASA. AAA tended to be statistically and independently associated with ASA (OR: 2.69, 95% CI : 0.97–7.47, p=0.05). Conclusions. We have demonstrated a higher incidence of mitral/aortic valvular regurgitations, AAA, PFO, and ASD in ASA patients compared to age- and gender-matched control group patients. In addition, we have shown that ASA is significantly and positively associated with mild mitral regurgitation and PFO.